Late Proton MR Spectroscopy in Children after Traumatic Brain Injury: Correlation with Cognitive Outcomes - Hunter, Jill V.; Thornton, Robert J.; Wang, Zhiyue J.; Levin, Harvey S.; Roberson, Garland; Brooks, William M.; Swank, Paul R. (American Journal of Neuroradiology, 2005)
BACKGROUND AND PURPOSE: Proton MR spectroscopy has demonstrated reduced levels of N-acetylaspartate (NAA) in normal-appearing occipital and frontal regions of patients with acute nonpenetrating traumatic brain injury (TBI). We studied the relationship of frontoparietal NAA, choline (Cho), and creatine (Cr) to test the hypothesis that reduction in NAA is predictive of cognitive outcome.METHODS: Proton spectra were collected by using conventional 2D chemical shift imaging in five healthy children and seven children (6 weeks to 3 years) with severe (n = 4), moderate (n = 2), or mild (n = 1) TBI. Spectra in the anterior and posterior regions of the left and right frontoparietal areas were averaged for analysis by using LCModel, with a phantom-established basis function, for quantification of NAA, Cho, and Cr concentrations. Intellectual function, expressive language, and arithmetic capability were measured within 4 months of imaging.RESULTS: NAA/Cho concentration was lower in TBI patients than in control subjects, but no group differences were present for Cho or Cr. Hemispheric levels for NAA, Cho, and Cr were higher on the left than on the right, but we found no effect of region and no interactions. Cognition was lower in the TBI group than the control group and correlated with NAA levels. Left frontal Cho was also correlated with arithmetic scores, whereas Cr was not significantly correlated.CONCLUSION: NAA levels remain low after TBI and are related to cognitive function. Neurometabolite values are greater in the left frontoparietal region than in the right, and the left frontal Cho level is related to arithmetic ability.